Selected Physical, Mechanical and Chemical Properties of Fresh Fruit Bunches for Processing of Palm Oil - ADETOLA, Olufemi Adeyemi (ABUAD Journal of Engineering and Applied Sciences, 2024)
Data on engineering properties of palm fruits enable the design of machinery for optimal production of palm oil. Specific physical, chemical, and mechanical characteristics of fresh fruit bunches are examined in this study. Fresh palm fruit’s selected mechanical, chemical, and physical characteristics were determined using standard formulas and equations. One hundred fresh fruit bunch samples were used to ascertain the physical characteristics of the fruit bunches. While the chemical properties were ascertained using suggested standard equations and formulae, the fresh fruit bunches were tested for their strength properties under compression when loaded under an INSTRON Universal Testing Machine. Using the Microsoft Excel program, statistical analysis was performed on the collected data. The average length, breadth, thickness, geometric mean, sphericity, surface area, true mass, true volume and true density mean for palm fruits were 3.35±0.48 cm, 1.92±0.32 cm, 2.24±0.33 cm, 2.42±0.25 cm, 0.73±0.08 cm, 18.61±3.62 cm2, 7.99±1.81 g, 7.01±1.72 cm3, 1.17±0.24 g/cm3 respectively. The average static coefficient of frictions for palm fruits were 0.46±0.13, 0.64±0.18, 0.57±0.21 and 0.59±0.22 while the average angle of reposes was 24.48±6.08, 31.62±9.14, 29.26±6.80, and 29.91±9.11 on wood, mild steel, glass and stainless-steel surface respectively. The energy at break, force at break, deformation at break, strain at break, and stress at break for the palm fruits were 6.87±0.95 J, 2.22±0.80 kN, 14.58±3.02 mm, 0.36±0.08 mm/mm and 123.46±44.31 MPa respectively. The moisture, ash, fat, crude fibre, crude protein, and carbohydrate contents (proximate composition) of the palm fruits were 22.80±0.02%, 0.52±0.01%, 46.47±0.06%, 18.66±0.01%, 2.4±0.21%, and 9.14±0.30% respectively. The sodium, potassium, calcium, magnesium, iron, phosphorus and zinc contents of the palm fruits were 58.75±0.07 ppm, 94.20±0.14 ppm, 68.45±0.64 ppm, 5.21±0.00 ppm, 1.22±0.00 ppm, 1.60±0.00 ppm and 55.70±0.28 ppm respectively. This study has provided relevant information which will help engineers to develop a more efficient palm fruit extraction machines that will in turn increase the productivity and profitability of the farmers and food processors. These measured engineering properties of palm fruits help in development of palm fruit processing machines.